Smart Skincare: Expert System Based on Certainty Factors for Skin Type Identification and Product Selection - Tar Muhammad Raja Gunung; Alyiza Dwi Ningtyas; Sengli Egani Sitepu; Vicky Rolanda; Abwabul Jinan (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study aims to develop an expert system for selecting skincare products based on skin type using the Certainty Factor method. This method is used to represent the expert's level of confidence in the symptoms that appear on the user's skin, so that the system can provide realistic diagnostic results that are close to human thinking. The research data was obtained through consultations with beauty experts and a review of dermatology literature. The test results show that the system is able to identify the user's skin type with varying degrees of certainty. For example, for patients with combination skin types, the system recommends appropriate skincare products such as Salicylic Acid Serum, Elshe Skin Acne Cleansing Wash, and Azarine Acne Gentle Cleansing Foam. Thus, this Certainty Factor-based expert system is expected to help individuals recognize their skin type and choose facial care products more accurately and effectively. Going forward, this system has the potential to be further developed with the integration of artificial intelligence technology and a broader product database to improve the accuracy and personalization of recommendations.